Climate Change and Adaptation Tries of Marginal Communities: A Case of Chepang and Tamang Communities in Nepal - Khatiwada, Kabita; Karki, Supendra; Koirala, Sunita; Ghimire, Diya (International Journal of Silkroad Institute of Research and Training, 2025)
Background: Climate Change is a serious problem emerging at a global, regional and local level. This study aims to analysis the climate change impact and adaptation measures taken by the Chepang and Tamang communities in Kalika municipality of Chitwan district in Nepal. Method: A cross sectional study design with purposive sampling of two communities Chepang and Tamang interviewed with Focus Group Discussion revealed information related to the Climate change impact and adaptation. The study were carried during March 2025, the interviewed script were processed and analyzed through Qualitative tools NVIVO and KII interview was taken with Local Government of Kalika, Division Forest Office and various stakeholders. Result: The study found that the heat and precipitation patters are changed from normal to erratic rainfall and excessive heat affected local production of the communities. Lack of Production, excessive inputs and improve verities seeds are the ongoing adaptation practices of the surveyed community. Traditional farming and market dependencies have increased due to climate change impact and slowly depletion of local production has now moved to the modern crop system. Low water and weather variation has disturbed the social, economic and cultural practices of the Chepang and Tamang communities. Conclusion: The study concluded as the climate change adversely affected the livelihood of the marginal communities and local adaptation measures are still traditional. A future sustainable development-based farming promotion like plantation of tree and local production enhancement are advised to manage the best sustainable development activities as the best alternative solution of climate change.